Use of ICT in Compulsory Secondary Education. Advantages and Disadvantages - García-Martín, Sheila; García-Martín, Judit (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The integration and use of ICT in educational centres is a complex process in which various factors intervene, such as the level of digital competence of teachers, technological infrastructure, and access to and use of the Internet. Hence, it is necessary to approach studies on ICT in education from multivariate approaches. In this sense, this study aims to know the use of five digital tools by 474 secondary school students in the classroom, to subsequently analyse the advantages and disadvantages of such use for their learning. The results are presented, and their implications are discussed.